β-Carotene adsorption on acid-activated montmorillonite - Güler, Çetin; SARIER, NİHAL (My University, 1988)
The adsorption of β-carotene from solution in benzene on acid-activated Canakkale montmorillonite of Turkey has been investigated. The adsorption isotherm had two steps. The first step was of the Langmuir type, and the isosteric heat of adsorption corresponding to this step was equal to −193.514 kJ/mol. The decrease in the total number of acid sites of the clay surface was determined to be 0.45×10−4 mol/g clay by nonaqueous titration with diethylamine. The phenomenon seems to be mainly a chemisorption stemming from the interaction of β-carotene with acid sites. Also, the activated clay acts as an oxidation catalyst on the β-carotene left in the solution.
Beta Carotene Adsorption on Acid Activated Montmorillonite
Keywords: Clay; Montmorillonite; Acid Site; Carotene; Azobenzene